Tebuthiuron com Carbofuran na cultura da cana-de-açúcar - Romão, Rodrigo Vieira (2008)
The sugarcane is one of most important cultures in Brazil, and is very important social and economically. The simultaneous use of nematicides with herbicides in sugarcane are growing every season, due to the positive along with productivities with the aim of these products. That coned responses in be explained due to high infestation of ectoparasitic nematode and weed in monoculture, when the application of these products is not accomplished. Some studies detected an interaction and a negative effect among the nematicides carbamates class, when they are associated to herbicides classified as substituted ureas. The objective this work was to study the biometricals and physiologicals parameters in cultivar RB72-454 in combined application with nematicide (Carbofuran) and herbicide (Tebuthiuron) with Al2(SO4)3 addition. The experiment was canned in pots of 20 L in greenhouse campus II - UNOESTE. In each recipients two stem were planted, with 20 cm of length. The treatments were the following: T1 - test; T2 - nematicide application carbofuran, at 2,975 kg a.i. for hectare; T3 - herbicide application (tebuthiuron), at 1 kg of a.i. for hectare; T4 nematicide application the carbofuran base, of 2,975 kg a.i. for hectare with application herbicide (tebuthiuron), at 1 kg of a.i. for hectare; T5 - nematicide application (carbofuran), at 2,975 kg a.i. for hectare with herbicide application (tebuthiuron), at 1 kg of a.i. for hectare, with more the addition of 27 mg Al for per kg of sail. In treatments of 600 kg was used by hectare of the formulation 8-28-16 as feeder. The work didn t show an interaction between Tebuthiuron and Carbofuran. A phytotoxic Tebuthiuron´s effect of was just detected with high sensibility equipments, and no Carbofuran´s phytotoxic effect was detected.